Application of singing method to improve memorization of asmaul husna for 1st grade students at kedungjati public elementary school - Annisa Fadhillah Hayya; Amir Mukminin; Zamzam Mustofa; Malikus Saleh (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2024)
The class action study conducted was intended to identify efforts to improve the quality of rote asmaul husna by using the method of singing. This use of the singing method has had a positive effect. From one cycle to the next, repairs were made. It makes it easier for students to memorize asmaul husna. By studying disciples, have indicated that application of the singing method has had a positive effect on learning asmaul husna in elementary school Kedungjati. Singing methods can improve participants' performance because they are active, creative and excited during the lesson. Studies have shown that the practice of singing to students successfully increases rote asmaul husna is performed at 33% precycle, in the I cycle is 58%, while in the II cycle increases 83%.